2018
DOI: 10.1177/0300060517750298
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of SIRT6 is associated with poor prognosis in patients with non-small cell lung cancer

Abstract: ObjectiveTo explore the prognostic significance of nicotinamide adenine dinucleotide (NAD)-dependent protein deacetylase sirtuin-6 (SIRT6), encoded by the sirtuin 6 (SIRT6) gene, in a population of Chinese Han patients with non-small cell lung cancer (NSCLC).MethodsCancer tissues and normal lung tissues (>5 cm adjacent to cancer tissue) were collected from Chinese Han patients with NSCLC. Expression levels of SIRT6 and histone H3-acetyl K56 (H3K56), in cancer and normal lung tissues from patients with NSCLC, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…The expression of SIRT6 is down-regulated in colon cancer, hepatocellular carcinoma, and head and neck squamous cell carcinoma [17]. Down-regulation of SIRT6 expression is associated with higher cancer staging and grades, as well as poor survival rates in cancer patients [18]. In contrast, SIRT6 expression is up-regulated in patients with prostate cancers, which is related to chemoresistance and poor prognosis in patients with cancer [19].…”
Section: Discussionmentioning
confidence: 99%
“…The expression of SIRT6 is down-regulated in colon cancer, hepatocellular carcinoma, and head and neck squamous cell carcinoma [17]. Down-regulation of SIRT6 expression is associated with higher cancer staging and grades, as well as poor survival rates in cancer patients [18]. In contrast, SIRT6 expression is up-regulated in patients with prostate cancers, which is related to chemoresistance and poor prognosis in patients with cancer [19].…”
Section: Discussionmentioning
confidence: 99%
“…These may be due to the differences of geography and cell lines in the selected samples of the studies. Some reports showed that SIRT6 was down‐regulated in NSCLC cells, 13 while some represented that SIRT6 was up‐regulated in NSCLC tissues and overexpression of SIRT6 was related to the poor prognosis of NSCLC 26 …”
Section: Discussionmentioning
confidence: 99%
“…Besides, Wang et al 12 discovered that overexpression of SIRT6 is able to inhibit the expression of HIF1α and VEGF, thereby restraining angiogenesis of lung cancer tumor. And Zhu et al 13 found that down‐regulation of SIRT6 expression is related to the poor prognosis of NSCLC, implying that SIRT6 has functions of controlling lung cancer development. Furthermore, it showed that overexpression of SIRT6 attenuates radioactive pneumonitis and lung injury 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Elaborating of the relationship between SIRT6 and NSCLC makes great sense for discovering a new biomarker for tumor targeting therapy 130 . Both the mRNA and protein SIRT6 levels were found downregulated in NSCLC tissue versus noncancerous tissue, and high expressions of SIRT6 appear to be favorable prognostic factors, indicating a tumor suppressor role of SIRT6 in NSCLC 87,131,132 . SIRT6 was firstly shown to suppress cell proliferation through downregulating the expression of oncogene Twist1 in NSCLC 87 .…”
Section: Human Diseasesmentioning
confidence: 99%